Perkembangan Hubungan Perkawinan: Kajian Tahap-Tahap Perkembangan Hubungan Antarpribadi pada Suami-Istri Katolik - Suryani, Anne (Jurnal Ilmu Komunikasi, 2004)
Focus of this research is the interpersonal relation growth phases in marriage at different marriage age. The analysis relies on the theory of The phases of interpersonal relation growth from Devito ( 2001), namely phase of Contact, Involvement, Intimacy, Deterioration, Repair, and Dissolution. Research shows that interpersonal relations of couple in Chatolic marriage develop through the phase: Contact, Involvement, Intimacy, Deterioration, and Repair phase. The Dissolution phase is not (yet) experienced by the informan because of principle of Chatolic marriage they believe. Marriage age does not relate to the relationship growth. The relationship growth itself varies in term of time, situation and process